2008
DOI: 10.1159/000142893
|View full text |Cite
|
Sign up to set email alerts
|

Genomic View of Energy Metabolism in <i>Ralstonia eutropha</i> H16

Abstract: Ralstonia eutropha is a strictly respiratory facultative lithoautotrophic β-proteobacterium. In the absence of organic substrates, H2 and CO2 are used as sole sources of energy and carbon. In the absence of oxygen, the organism can respire by denitrification. The recent determination of the complete genome sequence of strain H16 provides the opportunity to reconcile the results of previous physiological and biochemical studies in light of the coding capacity. These analyses revealed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 213 publications
5
127
0
1
Order By: Relevance
“…Three spots were identified to consist of proteins of energy metabolism, among these PntAa3, which is upregulated in mutant G ϩ 1 especially during cultivation with glucose; an equal quantity demonstrated one spot comprising three homologue proteins of PntAa, namely, PntAa3, PntAa2, and PntAa1. The PntAa proteins represent the alpha subunit of the membrane-bound NAD(P) transhydrogenases (PntAB) of R. eutropha H16 that couple the transfer of hydride ion equivalents between NADH and NADPH to proton translocation across a membrane (9,23,47). Two isoforms of the PHB granule-associated protein PhaP1 were increasingly expressed by mutant G ϩ 1 if glucose was provided; one spot containing two homologue proteins, PhaP1 and PhaP4, also showed greater quantities under the aforementioned conditions.…”
Section: Second Proteome Analysis (Analysis Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Three spots were identified to consist of proteins of energy metabolism, among these PntAa3, which is upregulated in mutant G ϩ 1 especially during cultivation with glucose; an equal quantity demonstrated one spot comprising three homologue proteins of PntAa, namely, PntAa3, PntAa2, and PntAa1. The PntAa proteins represent the alpha subunit of the membrane-bound NAD(P) transhydrogenases (PntAB) of R. eutropha H16 that couple the transfer of hydride ion equivalents between NADH and NADPH to proton translocation across a membrane (9,23,47). Two isoforms of the PHB granule-associated protein PhaP1 were increasingly expressed by mutant G ϩ 1 if glucose was provided; one spot containing two homologue proteins, PhaP1 and PhaP4, also showed greater quantities under the aforementioned conditions.…”
Section: Second Proteome Analysis (Analysis Ii)mentioning
confidence: 99%
“…Apparently, PntAa proteins form the respective domain I, and PntAb proteins form domain II. In contrast, the PntA4 region (H16_B1714, H16_B1715) may encode a soluble enzyme, since a distinct gene for domain II is absent (9). Alternatively, the aggregation in Ralstonia may take place as in E. coli, with domain II composed of subunit ␣ and ␤, as Ralstonia harbors putative existing membrane-spanning ␣ helices in the C-terminal region of PntA4.…”
Section: Vol 77 2011mentioning
confidence: 99%
“…Ralstonia eutropha H16 is a Gram-negative, rod-shaped, and facultative chemolithoautotrophic hydrogen-oxidizing bacterium and has served as a model organism for polyhydroxyalkanoate (PHA) metabolism and hydrogen-based chemolithoautotrophy for nearly 50 years (12,51). PHAs are accumulated as granules in the cytoplasm and serve the cells as storage compounds for carbon and energy.…”
mentioning
confidence: 99%
“…Recently, tungsten-dependent enzymes were also found in aerobic bacteria, e.g. in Methylobacterium extorquens (Laukel et al, 2003) or in R. eutropha (Cramm, 2009). In various studies it was shown that the interchange of molybdenum and tungsten led to inactive enzymes which can be exploited to identify whether the enzyme of interest is molybdenumor tungsten-dependent (May et al, 1988;McMaster & Enemark, 1998).…”
Section: Discussionmentioning
confidence: 99%